A reappraisal of the benefit‐risk profile of hydroxyurea in polycythemia vera: A propensity‐matched study. Issue 11 (29th July 2017) - Barbui, Tiziano; Vannucchi, Alessandro Maria; Finazzi, Guido; Finazzi, Maria Chiara; Masciulli, Arianna; Carobbio, Alessandra; Ghirardi, Arianna; Tognoni, Gianni
Abstract: The use of hydroxyurea (HU) as first line therapy in polycythemia vera (PV) has been criticized because no solid demonstration that this drug prevents thrombosis or prolongs survival has been so far produced. Here we present the outcomes of a large cohort of patients with PV included in the European Collaborative Low‐dose Aspirin (ECLAP) study. We selected 1, 042 patients who, during the follow‐up, had received only phlebotomy (PHL) or HU to maintain the hematocrit level < 45%. To assure comparability, we conducted a propensity score matching analysis. The two groups (PHL n  = 342 and HU n  = 681) were well balanced for the parameters included in the propensity score (overall balance: χ 2  = 2.44, P  = 0.964). Over a comparable period of follow‐up (PHL = 29.9 vs. HU = 34.7 months), we documented an advantage of HU over PHL consistently significant with respect to the incidence of fatal/non‐fatal cardiovascular (CV) events (5.8 vs. 3.0 per 100 person‐years in PHL vs. HU group, P  = 0.002) and myelofibrosis transformation that was only experienced by patients of PHL group. Evolution to acute leukemia was registered in three patients (two in PHL and one in HU group). The excess of mortality and total CV events in the PHL patients was restricted to the high‐risk group, and, compared with HU cases, was significant higher in the PHL patients who failed to reach the hematocrit target < 0.45% ( P  = 0.000). In conclusion, this analysis provides reliable and qualified estimates of the therapeutic profile of HU and PHL treatments for future experimental studies and for the management of PV in clinical practice.